Capacity of Antioxidants and Flavonoids Simplicia Pegagan Leaves Powder (Centella asiatica (l.) Urban) - Kartika Pratiwi, I Desak Putu; Wiadnyani, A.A. Istri Sri (Journal of Food Security and Agriculture, 2017)
Pegagan (Centella asiatica (L) Urban) is a herbal plant which is based on preclinical testing showed has an activity to increase intelligence through an antioxidant mechanism. The purpose of this research were to determine the effect of treatment blanching and drying methods on antioxidant activity, total phenolic content, total flavonoid content of Pegagan leaves. Pegagan leaf treatment consist of 2 factors, pretreatment (blanching, non blanching) and drying (oven, sunlight). The results of the study simplicia pegagan leaf powder has a value of total phenolic content from 124.98 to 219.45 mg GAE / 100g, total flavonoids content from 131.67 to 196.74 mgEK / 100g, and the antioxidant activity from 138.72 to 310.72 mgGAEAC / 100g. Blanching treatment at a temperature of 80°C for 60 seconds and drying in an oven at 50°C for 3 hours provides the highest antioxidant capacity value 310.72 mgGAEAC / 100g, total phenolic content 219.45 mg GAE / 100g, total flavonoid content 196.74 mgQE / 100g.